PENGEMBANGAN KOMIK DIGITAL DENGAN MODEL PROBLEM BASED LEARNING PADA MATA PELAJARAN PENDIDIKAN PANCASILA - Triana, Nur Wira (LPPM Universitas Muhammadiyah Muara Bungo, 2025)
A problem-based digital comic with a learning model is being developed to help students grasp Pancasila's ideals as a unity that is mutually animated and inspired by each principle. This research follows the 4D model (define, design, develop, and disseminate). A questionnaire was used to collect data from SDIT Al-Farabi teachers and fifth-graders. This research and development developed a digital comic on the relationship between Pancasila principles using Procreate version 5.3.14. At 90% and 93.8%, the material expert validator and media expert validated the digital comic as